2019
DOI: 10.15252/emmm.201809950
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of excitotoxicity‐induced processing of BDNF receptor TrkB‐FL leads to stroke neuroprotection

Abstract: Neuroprotective strategies aimed to pharmacologically treat stroke, a prominent cause of death, disability, and dementia, have remained elusive. A promising approach is restriction of excitotoxic neuronal death in the infarct penumbra through enhancement of survival pathways initiated by brain‐derived neurotrophic factor (BDNF). However, boosting of neurotrophic signaling after ischemia is challenged by downregulation of BDNF high‐affinity receptor, full‐length tropomyosin‐related kinase B (TrkB‐FL), due to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 92 publications
3
31
0
Order By: Relevance
“…Thus, we used BDNF to stimulate eNOS-dependent neuroprotective NO synthesis in our cell model 16 . Consistent with our results, the restitution of BDNF/TrkB signaling after a stroke enhanced neuroprotection in the cerebral cortex 58 . Moreover, further recent studies have confirmed the functional implications of eNOS expression in neurons 59 .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we used BDNF to stimulate eNOS-dependent neuroprotective NO synthesis in our cell model 16 . Consistent with our results, the restitution of BDNF/TrkB signaling after a stroke enhanced neuroprotection in the cerebral cortex 58 . Moreover, further recent studies have confirmed the functional implications of eNOS expression in neurons 59 .…”
Section: Discussionsupporting
confidence: 92%
“…In support, we showed that microglia and astrocyte-induced neuroinflammation plays a crucial role in the development of POCD. Moreover, alteration in BDNF signaling can result in synaptic dysfunction that is associated with memory deficits observed in AD [48], Parkinson's disease (PD) [41], stroke [49], and sepsisassociated encephalopathy [50]. In the present study, we showed that anesthesia and surgery induced decreased levels of BDNF, which could be reversed by memantine and MDL-28170.…”
Section: Discussionmentioning
confidence: 47%
“…The protocol was as previously reported with slight modifications. 31,32 Briefly, E17-18 fetuses from the same pregnant Sprague-Dawley rat were used for primary cultures of cortical neurons. Brains were carefully dissected with fine scissors, and cortices were isolated and the meninges were removed with fine forceps in ice-cold DMEM.…”
Section: Primary Rat Cortical Neuron Culturementioning
confidence: 99%